The influence of the El Niño phenomenon on appearance of large-scale forest fires and their ecological consequences - L. F. Chernogor; A. N. Nekos; G. V. Titenko; L. L. Chornohor (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія)
The frequency and intensity of forest fires is increasing year by year. It is due to global warming, which is associated with both natural and anthropogenic phenomena and processes There is another mechanism of global impact on the weather, abnormally high summer temperatures, severity and frequency of droughts, intensity and frequency of forest fires and their consequences. It is associated with the unique, cyclical, natural phenomenon of El Niño. The possibility of this phenomenon influence on the intensity of large-scale forest fires and their ecological consequences cannot be excluded, in accordance with the analysis of these processes and their quantitative assessment. There is reason to believe that the phenomenon may affect the intensity and frequency of forest fires in countries nearby. Such a country is, in particular, Chile, which experiences intense forest fires every year. Their intensity is compared to the intensity of record fires in Ukraine in 2020.